Nanoparticle Interactions with the Immune System: Clinical Implications for Liposome-Based Cancer Chemotherapy - La-Beck, Ninh M.; Gabizon, Alberto A. (Frontiers in Immunology, 2017)
The development of stable and long-circulating liposomes provides protection of the drug cargo from degradation and increases tumor drug delivery, leading to the design of liposome formulations with great potential in cancer therapy. However, despite the sound pharmacologic basis, many liposomal as well as other nanoparticle-based drug formulations have failed to meet regulatory criteria for approval. The question that arises is whether we have missed key liposome-host interactions that can account for the gap between the major pharmacologic advantages in preclinical studies and the modest impact of the clinical effects in humans. We will discuss here the nanoparticle-immune system interactions that may undermine the antitumor effect of the nanodrug formulations and contribute to this gap. To overcome this challenge and increase clinical translation, new preclinical models need to be adopted along with comprehensive immunopharmacologic studies and strategies for patient selection in the clinical phase.